Protocols for Personal Protective Equipment in a COVID-19 Medical Shelter. (14th August 2020) - Hockaday, Sarah; Krause, Kate; Sobieski, Catherine; Li, Jeffrey N.; Hurst, Rachel; Ryan, Benjamin; Leader, Michael; Smith, Dustin; Fowler, Ray; Tran, Andrew; McMullan, Stephen; Hogan, Andrew; et al.
Abstract: The coronavirus disease 2019 (COVID-19) has greatly impacted health-care systems worldwide, leading to an unprecedented rise in demand for health-care resources. In anticipation of an acute strain on established medical facilities in Dallas, Texas, federal officials worked in conjunction with local medical personnel to convert a convention center into a Federal Medical Station capable of caring for patients affected by COVID-19. A 200, 000 square foot event space was designated as a direct patient care area, with surrounding spaces repurposed to house ancillary services. Given the highly transmissible nature of the novel coronavirus, the donning and doffing of personal protective equipment (PPE) was of particular importance for personnel staffing the facility. Furthermore, nationwide shortages in the availability of PPE necessitated the reuse of certain protective materials. This article seeks to delineate the procedures implemented regarding PPE in the setting of a COVID-19 disaster response shelter, including workspace flow, donning and doffing procedures, PPE conservation, and exposure event protocols.